Utilization of Blast Furnace Solid Waste (Slag) As Cement Substitution Material on Mortar Manufacture - Amin, Muhammad; Isnugroho, Kusno; Hendronursito, Yusup (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2018)
Slag is defined as a waste material produced from iron ore smelting process in blast furnace. The slag was derived from Research Center for Mineral Technology located in Tanjung Bintang Lampung Selatan with particle size of 80,100, and 120 mesh. The percentages of slag used as cement substitution were 10%, 20%, and 30% from total volume. Test pieces was made by compressing all mixture material in 50 x 50 x 50 mm cubical mortar mold. Physical test of mortars, such as : porosity test, density test and compressive strength test were performed. Based on physical test of samples, it was shown that the higher ratio of slag used in cement substitution gives higher mortar porosity. Substitution of 10% slag with size of 100 mesh produced the porosity of 3.45%, while the substitution 20% and 30% slag with the same size, produced 5.08% and 5.76% porosity, compared with the standard of mortar which was 5.12%. The compressive strength test with 10% slag substitution was 19.3 Mpa, while 20% substitute slag gave the compressive strength of 19.1 Mpa and 30% substitute slag has compressive strength value of 18.7 Mpa. The standard mortar is 17.2 Mpa. However, beside of slag substitution ratio, the slag particle size also affected the compressive strength and porosity. Based on the results explained, the substitution of slag as a substitute for cement in mortar strength was still above the mortar standard.